Kondisi fisik kelautan habitat ditemukannya Latimeria menadoensis di selatan Teluk Manado - Isti Utami Indah Sari Ali; Kawilarang W. A. Masengi; Lusia Manu; Alfret Luasunaung; Janny F. Polii; Revols D. Ch Pamikiran; Arman Thamin (Universitas Sam Ratulangi, 2019)
The movement of the water mass on the ocean or known as current is a very complex natural phenomenon. That related to the variation of the controlling factors. This research was based on descriptive method to obtain the information about the problem being studied.Â Data collected by operating the three oceanographic tools that area floater current meter, tidal gauges, and wave gauges. Data collection were carried out during the day and night of two locations which tidal and wave high were measured at 1O 27 '39.90